(untitled) (Research, Society and Development, 2020)
One of the great challenges for teachers working in professional education is to bring the labor market closer to the subjects studied in the classroom. Thus, the objective of this work was to propose a case study with a different methodology, applied in the discipline of Regional Chemical Technologies of the Technical Course of Medium Level in Chemistry, Subsequent modality, of the Federal Institute of Rio Grande do Norte (IFRN), campus Apodi. The method was based on technical visits covering all the contents of the discipline’s menu. In this way, each class was structured in three phases, the first being called pre-visit, containing the planning of the visit and the exposure of the theoretical content in the classroom. The second stage was the visit, in which they met companies to produce mineral water, water, and sewage treatment, shrimp farming, ceramics, brewery, sweets, pasteurized milk, fruit pulp, salt, steel, and an educational and research institution. In the third phase, categorized as post-visit, students held a seminar on one of the segments visited, followed by a conversation circle, in which they debated the aspects observed during field classes. At the end of the semester, to know the students’ perceptions regarding the impact of these classes on their training, and the evaluation of the methodology proposed by the discipline’s teacher, a questionnaire was applied using the Likert scale. With the compilation and analysis of the responses, all participants agreed that the proposed method was adequate and that it had importance in academic and professional training.